Glass houses - Szmuryło, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
It’s about, how glass houses look like today, if they are neglected remnants of past times. Has this idea survived to our times, maybe launched something new or evolved? Is a transparency of residential architecture needed in a such extent? It’s also about opportunities, that are given to us by glass, which is still a material bringing to perfection with almost unlimited applications for the purpose of developing trends of architecture, and above all human needs. Grimshaw provides that “in future, we will not design buildings, but organisms able to change and adapt to the extent compatible with the technology of the time, in which we find ourselves”. Houses must be functional, intelligent and beautiful. This is a place where we can relax, have a sense of privacy and security. Attempts to renew our relationship with nature are always regardless of where and how we live. Man wants to enjoy the view, feels flurry of wind and have lots of sun.